An International Multispecialty Validation Study of the IgG4‐Related Disease Responder Index. Issue 11 (26th October 2018) - Wallace, Zachary S.; Khosroshahi, Arezou; Carruthers, Mollie D.; Perugino, Cory A.; Choi, Hyon; Campochiaro, Corrado; Culver, Emma L.; Cortazar, Frank; Della‐torre, Emanuel; Ebbo, Mikael; Fernandes, Ana; Frulloni, Luca; et al.
Abstract : Objective: IgG4‐related disease (IgG4‐RD) can cause fibroinflammatory lesions in nearly any organ, leading to organ dysfunction and failure. The IgG4‐RD Responder Index (RI) was developed to help investigators assess the efficacy of treatment in a structured manner. The aim of this study was to validate the RI in a multinational investigation. Methods: The RI guides investigators through assessments of disease activity and damage in 25 domains, incorporating higher weights for disease manifestations that require urgent treatment or that worsen despite treatment. After a training exercise, investigators reviewed 12 written IgG4‐RD vignettes based on real patients. Investigators calculated both an RI score as well as a physician's global assessment (PhGA) score for each vignette. In a longitudinal assessment, 3 investigators used the RI in 15 patients with newly active disease who were followed up over serial visits after treatment. We assessed interrater and intrarater reliability, precision, validity, and responsiveness. Results: The 26 physician investigators included representatives from 6 specialties and 9 countries. The interrater and intrarater reliability of the RI was strong (0.89 and 0.69, respectively). Correlations (construct validity) between the RI and PhGA were high (Spearman's r = 0.9, P < 0.0001). The RI was sensitive to change (discriminant validity). Following treatment, there was significant improvement in the RI score (mean change 10.5 [95% confidence interval (95% CI) 5.4–12], P < 0.001), which correlated with the change in the PhGA. Urgent disease and damage were captured effectively. Discussion: In this international, multispecialty study, we observed that the RI is a valid and reliable disease activity assessment tool that can be used to measure response to therapy.